KARAKTERISTIK DAN DAMPAK SIKLON TROPIS YANG TUMBUH DI SEKITAR WILAYAH INDONESIA - Dewi Surinati; Dwi Ayu Kusuma (Pusat Penelitian Oseanografi LIPI, 2018)
CHARACTERISTICS AND IMPACTS OF TROPICAL CYCLONES GROWING AROUND INDONESIAN TERRITORY. Tropical cyclone is a cyclonic originates from tropical oceans and driven principally by heat transfer from the ocean. Tropical cyclone is an atmospheric phenomenon characterized by the emergence of low air pressure that triggers the occurrence of strong winds due to the process of heat transfer from the equator to the latitude. This phenomenon can not be prevented, so that it has great potential to impact on the damage in the area it through. Tropical cyclones can be characterized through their life cycle, scale of power and how it impacts in the area it through. The Cempaka and Dahlia tropical cyclone occuring in 2017 greatly influenced territory of Indonesia. The effect of the cyclone causes extreme weather in Indonesia, especially in areas close to where cyclones are formed.